Preliminary studies of radiation coupling between remote soft X-ray laser amplifiers - Cairns, G; Lewis, C; MacPhee, A; Neely, D; Holden, M; Krishnan, J; Tallents, G; Key, M; Norreys, P; Smith, C; Zhang, J; Holden, P; et al. (Springer-Verlag, 1994)
Coupling of a soft X-ray laser beam with a relaying concave mirror in a sequentially pumped amplifier geometry using the Ne-like Ge system has been studied experimentally. Preliminary observations indicate an increase in the spatial coherence of the amplified relayed beam. In addition, near-field imaging of one of the amplifier plasmas shows a double-lobed intensity pattern of the emergent beam indicating refractive guiding of the amplified beam with components both normal and tangential to the target surface. © 1994 Springer-Verlag.